Global dimensions of intellectual property rights in science and technology - Wallerstein, Mitchel B.; Mogee, Mary Ellen; Schoen, Roberta A.; National Academy of Sciences (U.S.); National Research Council (U.S.). Office of International Affairs (Washington, DC : National Academy Press, 1993)
Annotation This volume offers an update on current international intellectual property rights (IPRs) negotiations and includes case studies on software, computer chips, optoelectronics, and biotechnology. The volume covers these and other issues: (1) Modern economic theory as a basis for approaching international IPRs; (2) U.S. intellectual property practices versus those in Japan, India, the European Community, and the developing and the newly industrializing countries; (3) Pros and cons of a uniform international IPRs regime versus a system reflecting national differences. Index. Approx.
Sectoral views : the research university / John T. Preston -- The federal government / Bruce Merrifield -- U.S. industry / George W. McKinney III -- Intellectual property rights and competitive strategy : a multinational pharmaceutical firm / Otto A. Stamm -- A multinational electronics firm / Michiyuki Uenohara -- The Mexican software industry / Antonio Medina Mora Icaza -- A multinational telecommunications firm / William L. Keefauver -- Adapting the intellectual property system to new technologies / John H. Barton -- A case study on computer programs / Pamela Samuelson -- Biotechnology case study / George B. Rathmann -- Semiconductor chip protection as a case study / Morton David Goldberg -- Optoelectronics / Eugene I. Gordon.
Includes bibliographical references and index.
"Based ... on the proceedings of the conference ... held at the National Academy of Sciences on January 8-9, 1992"--Page vii.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Intellectual property -- Congresses; Technology and law -- Congresses; Intellectual property; Intellectual Property; Propriété intellectuelle -- Congrès.; Technologie et droit -- Congrès.; Propriété intellectuelle; intellectual property; POLITICAL SCIENCE; Public Policy / Economic Policy; LAW -- International; Intellectual property; Technology and law; Geistiges Eigentum; Internationales Patentrecht; Internationales Urheberrecht; Wissenschaft; Kongress; Recht van de intellectuele eigendom; Internationalisatie; Kennisoverdracht; Congress; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings; Actes de congrès.